2008
DOI: 10.1111/j.1438-8677.2008.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors regulating leaf senescence in Arabidopsis thaliana

Abstract: Senescence is a highly regulated process, eventually leading to cell and tissue disintegration: a physiological process associated with nutrient (e.g. nitrogen) redistribution from leaves to reproductive organs. Senescence is not observed in young leaves, indicating that repressors efficiently act to suppress cell degradation during early leaf development and/or that senescence activators are switched on when a leaf ages. Thus, massive regulatory network re‐wiring likely constitutes an important component of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
308
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(318 citation statements)
references
References 67 publications
8
308
1
1
Order By: Relevance
“…SGR, NYC1, PPH, PAO and MES16 (Ren et al 2007(Ren et al , 2010Schelbert et al 2009;Pružinská et al 2005;Horie et al 2009;Christ et al 2012) are highly coregulated in Arabidopsis and consequently cluster closely together when performing gene network analyses, for example using the ATTEDII platform (Obayashi et al 2009). Possibly, among the hundreds of transcription factors that have been shown to be up-regulated during leaf senescence (Balazadeh et al 2008) are some that specifically target the PAO pathway, but these have so far not been identified.…”
Section: Gene Regulationmentioning
confidence: 99%
“…SGR, NYC1, PPH, PAO and MES16 (Ren et al 2007(Ren et al , 2010Schelbert et al 2009;Pružinská et al 2005;Horie et al 2009;Christ et al 2012) are highly coregulated in Arabidopsis and consequently cluster closely together when performing gene network analyses, for example using the ATTEDII platform (Obayashi et al 2009). Possibly, among the hundreds of transcription factors that have been shown to be up-regulated during leaf senescence (Balazadeh et al 2008) are some that specifically target the PAO pathway, but these have so far not been identified.…”
Section: Gene Regulationmentioning
confidence: 99%
“…SAGs encoding hydrolytic enzymes as well as transporters have been identified to be responsible for either the degradation or mobilization of the various macromolecules and breakdown products. In addition, many transcription factors are expressed that coordinate this complex developmental process (Nam, 1997;Lers et al, 1998;Thompson et al, 1998;Rubinstein, 2000;Bhalerao et al, 2003;Buchanan-Wollaston et al, 2003, 2005Gepstein et al, 2003;Yoshida, 2003;Guo et al, 2004;Balazadeh et al, 2008). As well as developmental leaf senescence, adverse biotic or abiotic conditions can interfere with or induce senescence (Gregersen et al, 2013).…”
mentioning
confidence: 99%
“…Early expression profiling and transcriptome analyses have revealed that a big portion of specific transcription factors are reprogrammed during leaf senescence (Chen et al, 2002;BuchananWollaston et al, 2003BuchananWollaston et al, , 2005Guo et al., 2004;Zentgraf et al., 2004;Balazadeh et al., 2008;Breeze et al, 2011). These transcription factors are characterized in the protein families NAC, WRKY, MYB, C2H2 zinc finger, bZIP, and AP2/EREBP.…”
mentioning
confidence: 99%